A Reuse Evaluation for Solar-Cell Silicon Wafers via Shift Revolution and Tool Rotation Using Magnetic Assistance in Ultrasonic Electrochemical Micromachining - P. S. Pa (International Journal of Photoenergy)
A new reuse fabrication using a tool module with rotation and revolution through a process of magnetic assistance in ultrasonic electrochemical micromachining (UEMM) for removal of the surface layers from silicon wafers of solar cells is demonstrated. The target of the proposed reuse fabrication method is to replace the current approach, which uses strong acid and grinding and may damage the physical structure of silicon wafers and pollute to the environment. A precisely engineered clean production approach to removal of surface microstructure layers from silicon wafers is to develop a mass production system for recycling defective or discarded silicon wafers of solar cells that can reduce pollution and cost. The high revolution speed of the shift with the high rotation speed of the designed tool increases the discharge mobility and improves the removal effect associated with the high feed rate of the workpiece. High frequency and high power of ultrasonic with large electrolyte flow rate and high magnetic strengths with a small distance between the two magnets provide a large discharge effect and good removal; only a short period of time is required to remove the epoxy film and Si3N4 layer easily and cleanly.